(untitled) (Homoeopathy for All, 2024)
Hair is almost like a social status for both men and women, and also children. Hair loss can affect scalp or entire body. Anyone like men, women and children can experience hair loss. Baldness typically refers to excessive hair loss from scalp. Hereditary hair loss with age is the most common cause of baldness. Some people prefer to let their baldness run its course untreated and unhidden. It can be the result of heredity, hormonal changes, medical conditions or medications. Homoeopathy is considered as one of the very best alternative system for treating hair loss.